Faktor Faktor yang Mempengaruhi Perilaku Lansia dalam Mengikuti Senam Lansia di Wilayah Kerja Puskesmas - Novianti Novianti; Dina Mariana (Jurnal Keperawatan Silampari, 2018)
This study aims to determine the factors that influence the behavior of the elderly in following the elderly exercise at Jalan Gedang Health Center in Bengkulu City. This study is an analytic study with a cross-sectional design. The results showed that the majority of respondents (60.6%) had less knowledge, most respondents (51.5%) received lower family support, almost half the respondents (36.4%) had low motivation, almost half the respondents (42 , 4%) did not actively behave in participating. on gymnastics for the elderly, and the results of the chi-square value Ï = 0.040, 0.000 and 0.001. Conclusion, there is a relationship between knowledge, family support and motivation towards the behavior of the elderly in participating in gymnastics at Jalan Gedang Health Center in Bengkulu City. Keywords: Family Support Awareness, Motivation and Behavior